Effectiveness of Anthropometric Measurements for Identifying Diabetes and Prediabetes among Civil Servants in a Regional City of Northern Ethiopia: A Cross-Sectional Study. (7th April 2020) - Woldegebriel, Ataklti Gebertsadik; Fenta, Kiros Ajemu; Aregay, Asfawosen Berhe; Aregay, Abraham Desta; Mamo, Nega Bezabih; Wubayehu, Tewolde Woldearegay; Bayray, Alemayehu; Mulugeta, Afework
Abstract : Back ground . Diabetes mellitus is an emerging noncommunicable disease in Ethiopia. Overlooking an appropriate tool for identifying diabetes and prediabetes would have significant impact for future diabetes and prediabetes projections and its management. Therefore, the study aims to examine the effectiveness of anthropometric measurements for identifying prediabetes and diabetes in Mekelle city, Tigray, Northern Ethiopia. Methods . The study involved a cross-sectional survey carried out from October 2015 to February 2016 among 1504 subjects aged from 18 to 75 years of age. Receiver operating characteristic (ROC) was used to select the most effective anthropometric cut-off point among waist circumference, waist-to-hip ratio, waist-to-height ratio, and BMI for identifying prediabetic and diabetes. Statistical significance was declared at p value of ≤0.05. Results . Waist circumference was found better for identifying diabetes (AUC = 0.69) and prediabetes (AUC = 0.63) in women, respectively. Waist-to-hip ratio was better identifying diabetes (AUC = 0.67) while waist circumference-to-height ratio was better identifying prediabetes (AUC = 0.63) in men compared to body mass index. The optimal cut-off point with maximum sensitivity and specificity of waist circumference for identifying diabetes and prediabetes was 83.5 cm and 82.9 cm in women, respectively. The optimal ut-off point with maximum sensitivity and specificity of waist-to-hip ratio for identifying diabetes and prediabetes was 0.97 and 0.82 in men, respectively. Conclusion . Waist circumference and waist-to-hip ratio exhibited better discriminate performance than BMI for identifying prediabetes and diabetes in women and men, respectively.